The effect of Indomie advertising on Instagram on purchase decisions (survey on Instagram account @indomie) - rifqi, Rifqi Alamsyah Chaidir; purnamasari, Oktaviana Purnamasari (COMMICAST, 2022)
Indomie is an instant noodle product brand that has existed since 1971, even this brand has been embedded in people's minds, so it is often found that the Indomie brand is no longer a brand but also a name for instant noodle products. One of the advertisements displayed on Instagram @Indomie is an advertisement about a new variant, namely Indomieghetti Bolognese, which informs about a new variant or innovation of Indomie. This study aims to determine the effect of Indomie Advertising version of Indomieghetti Bolognese on purchasing decisions. The theory used is advertising theory from Kotler and Keller which has informative, persuasive, reminder, and reinforcement dimensions. Then the Purchasing Decision theory from Kotler and Armstrong with the dimensions of need recognition, information search, evaluation of alternatives, purchase decisions, and postpurchase behavior. This research is a quantitative research with survey methods and data collection techniques using qff1uestionnaires. The population of this study is Instagram @Indomie's active followers who commented on the upload of March 15, 2021, as many as 156 followers and the sample used is 61 respondents, which is calculated using the Slovin formula. The sampling technique used in this study was Simple Random Sampling. The results of this study indicate that there is an influence of Indomieghetti Bolognese ads on Instagram on purchasing decisions of 0.601 or 60.1% while the remaining 39.9% is influenced by other variables other than those in this study.